Agapornis sp. pet birds: Source of dissemination of azole-resistant yeasts. (4th August 2018) - Reis, Eduardo J C; Buscariolo, Fabio; Siqueira, João P Z; Castilho, Elza M; Almeida, Margarete T G
Abstract: The objectives of this study were to identify yeasts in 40 feces samples of Agapornis birds and determine their antifungal susceptibility profile by two methodologies. Results indicated 92.5% of positivity (46 isolates). Six genera were identified (14 species): Cryptococcus (39.13%), four species; Candida (36.96%), four species; Rhodotorula (13.05%), two species; Trichosporon (6.52%), two species; Kodamaea ohmeri (2.17%); and Sporobolomyces salmonicolor (2.17%). Regarding the susceptibility profiles, 41.3% of the isolates showed low sensibility to fluconazole and 47.8% to itraconazole. Thus, Agapornis sp. disseminate potentially pathogenic and resistant yeasts. Precautionary measures should be taken regarding breeding and keeping them as pets.